Gas Explosion and Its Protection Technology in Process Industries - Wang, Zhirong; Cao, Xingyan; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2025)
This open access book first introduces the explosive characteristics of combustible gas in the process industrial device, and then introduces the influence law of structural effect on gas explosion characteristics and deflagration to detonation process, and finally introduces the suppression mechanism and protection technology of gas explosion. This book takes the process industrial gas explosion characteristics and its protection as the research object, and discusses the gas explosion characteristics and its protection theory in details. This book can be used as the undergraduate and graduate textbook of safety engineering and related engineering majors in universities, and also as a reference for scientific research staff in safety science and engineering and related disciplines, and also for the reference of safety technology and management personnels.
Introduction -- Gas explosion characteristics in the confined spaces -- Structure effect of connected vessels on gas explosion characteristics -- Scale effect of gas explosion in the confined space -- DDT propagation characteristics of gas explosion inside the vessel.
Accessibility summary: This PDF does not fully comply with PDF/UA standards, but does feature limited screen reader support, described non-text content (images, graphs), bookmarks for easy navigation and searchable, selectable text. Users of assistive technologies may experience difficulty navigating or interpreting content in this document. We recognize the importance of accessibility, and we welcome queries about accessibility for any of our products. If you have a question or an access need, please get in touch with us at accessibilitysupport@springernature.com.
No reading system accessibility options actively disabled
Publisher contact for further accessibility information: accessibilitysupport@springernature.com
Keywords: Chemical engineering; Underground construction; Chemicals -- Safety measures; Petrology; Manufactures; Chemical Process Engineering; Underground Engineering and Tunnel Construction; Chemical Safety; Petrology; Machines, Tools, Processes